A joint age-based system replacement and component reallocation maintenance policy: Optimization, analysis and resilience. (July 2023) - Fu, Yuqiang; Zhu, Xiaoyan
Highlights: Proposed an age-based joint system replacement and component reallocation policy. Addressed that components are failure-undetectable and unevenly degraded. Established an integrated optimization model for a system with an arbitrary structure. Derived analytical results and compared results with an age-based replacement policy. Showed effects of the policy on maintenance cost and resilience by numerical studies. Abstract: The component reallocation (CR) policy is an emerging and effective preventive maintenance policy for improving the system performance, which has attracted much attention in reliability engineering and is independent from the research of age-based system replacement (ASR). This paper is to explore advantages and characteristics of a joint ASR and CR (JASRCR) preventive maintenance policy for a system, for which it is hard or uneconomical to execute repair or replacement at the component level but easy to reallocate the functionally-interchangeable and unevenly degraded components. In the JASRCR policy, the CR is implemented before the system failure and preventive ASR, and the corrective maintenance is to replace the system whenever it fails. The CR is of capability of balancing the degradation processes of components and thus has potential on improving the system resilience in resisting the component failures. An integrated mixed binary nonlinear optimization model is proposed to determine the optimal assignment of CR and optimal times for ASR and CR with the objective of minimizing the expected total maintenance cost per unit time. Numerical experiments demonstrate efficiency of the JASRCR policy on improving system resilience and reducing system maintenance cost.